Kampanye Sosial Ruang Publik yang Aman dan Inklusif untuk Perempuan dalam Perspektif Islam - Haris, Thifal Fadhil; Setiawati, Titin; Mustiawan, Mustiawan (UIN Sunan Ampel Surabaya, 2026)
Public spaces are social interaction arenas that should ideally be safe and inclusive for all members of society, including women. However, in practice, women still frequently experience violence, harassment, and discrimination in public spaces, which reduces their sense of safety and limits their social participation. This condition reflects an academic concern regarding the low level of public awareness about the importance of safe and inclusive public spaces.This study aims to analyze the social campaign conducted by INFID through the Human Rights Festival (Festival HAM) program in raising public awareness of this issue. This research employs a qualitative approach with a case study method. Data collection techniques include in-depth interviews, observation, and documentation, involving informants consisting of the organizers and participants of the Human Rights Festival. Data analysis uses the interactive model of Miles and Huberman and is validated through source triangulation to ensure data reliability. The results show that the INFID Human Rights Festival social campaign was implemented through four stages based on Ostergaard’s social campaign theory: problem identification, planning, campaign management, and problem reduction. In the identification stage, it was found that low public awareness and the limited availability of safe spaces for women were the main background issues of the campaign. In the planning stage, strategies were focused on the younger generation through an event-based campaign approach combined with social media. In the management stage, the campaign was realized through participatory activities such as discussions, workshops, and exhibitions. Meanwhile, in the problem reduction stage, there was an increase in awareness, changes in perspectives, and early indications of reducing the contributing factors of the problem. The social campaign through the INFID Human Rights Festival is considered effective as a public communication strategy in building public awareness of the importance of safe and inclusive public spaces for women. From an Islamic perspective, social campaigns are communication processes aimed at encouraging society toward good (amar ma’ruf) and preventing wrongdoing (nahi munkar), using persuasive and educational approaches to promote positive behavioural change.